Augmented Reality versus Virtual Reality for 3D Object Manipulation - Krichenbauer, Max; Yamamoto, Goshiro; Taketom, Takafumi; Sandor, Christian; Kato, Hirokazu (IEEE transactions on visualization and computer graphics, 2018)
Virtual Reality (VR) Head-Mounted Displays (HMDs) are on the verge of becoming commodity hardware available to the average user and feasible to use as a tool for 3D work. Some HMDs include front-facing cameras, enabling Augmented Reality (AR) functionality. Apart from avoiding collisions with the environment, interaction with virtual objects may also be affected by seeing the real environment. However, whether these effects are positive or negative has not yet been studied extensively. For most tasks it is unknown whether AR has any advantage over VR. In this work we present the results of a user study in which we compared user performance measured in task completion time on a 9 degrees of freedom object selection and transformation task performed either in AR or VR, both with a 3D input device and a mouse. Our results show faster task completion time in AR over VR. When using a 3D input device, a purely VR environment increased task completion time by 22.5 percent on average compared to AR ( {p}<0.024 <inline-graphic xlink:href="krichenbauer-ieq1-2658570.gif"/> ). Surprisingly, a similar effect occurred when using a mouse: users were about 17.3 percent slower in VR than in AR ( {p}<0.04 <inline-graphic xlink:href="krichenbauer-ieq2-2658570.gif"/> ). Mouse and 3D input device produced similar task completion times in each condition (AR or VR) respectively. We further found no differences in reported comfort.